Limb‐girdle muscular dystrophy: A perspective from adult patients on what matters most. Issue 4 (24th July 2019) - Hunter, Michael; Heatwole, Chad; Wicklund, Matthew; Weihl, Conrad C.; Mozaffar, Tahseen; Statland, Jeffrey M.; Johnson, Nicholas E.
Abstract: Introduction: Limb‐girdle muscular dystrophy (LGMD) consists of over 30 genetic conditions with varying clinical phenotypes primarily affecting pelvic girdle, shoulder girdle, and other proximal limb muscles. Studies focusing on the physical, mental, and social effects of this disease from the patient's perspective are limited. Methods: Adults with LGMD were interviewed and asked to identify issues that have the greatest impact on their quality of life. Each interview was recorded, transcribed, coded, and analyzed. Results: Participants provided 1385 direct quotes. One hundred sixty‐five potential symptoms of importance were identified and grouped into 15 larger themes. The most frequently reported themes included limitations with mobility, difficulty performing activities, social role limitations, and emotional distress. Discussion: There are multiple symptoms that alter the lives of adults with LGMD. These affect their physical, emotional, and social health, and may be amenable to medical intervention.